Intranet-based Memo Automation System / Zalina Abd Razak - Abd Razak, Zalina (2000)
Memo Automation is one of the modules that can be found in a typical Office Automation System. The job is to handle and circulate memo among the users and is to be used in an office or an organization. With the need of computerization, memo automation system is basically one of the tools to enhance the level of communication among the users. And by making it an Intranet-based system, this will widen the scope of interaction, which can be developed among the user of the system. Basically Memo Automation System covers the mechanism of handling and circulating memo on-line. Apart from employing the desktop concept, the system works with the webtop concept whereby all the required information is being prepared on the web and ready to be used by the respective users. The Intranet-based memo automation system is somehow new to the idea of a paperless environment of the borderless world today. Therefore, with the invention of one will definitely helps the respective users to do management tasks, especially within the office environment.